Predicting the radiosensitivity of HPV-negative oropharyngeal squamous cell carcinoma using miR-130b. (1st June 2021) - Inoue, Hitoshi; Hirasaki, Masataka; Kogashiwa, Yasunao; Kuba, Kiyomi; Ebihara, Yasuhiro; Nakahira, Mitsuhiko; Sakai, Akihiro; Okuda, Akihiko; Sugasawa, Masashi
Abstract: Background: Human papillomavirus (HPV)-negative oropharyngeal squamous cell carcinoma shows a higher rate of radiation resistance than HPV-positive oropharyngeal squamous cell carcinoma (OPSCC). Radioresistant HPV-negative OPSCC is associated with unfavourable outcomes, but validated prognostic biomarkers remain lacking. Aims/Objectives: This study investigated biomarkers for radioresistant HPV-negative OPSCC. Material and methods: The Cancer Genome Atlas included miRNA sequence and mRNA sequence data from 528 HNSCC tumours. Of these, we used gene expression data for HPV-negative head and neck squamous cell carcinoma for which data were available on the effects of radiation, and compared miRNA sequence and mRNA sequence data between radioresistant and radiosensitive groups. We subsequently estimated downstream miRNA from the results. Finally, we validated miRNAs related to the outcomes of radiotherapy in our clinical cases. Results: Investigation of miRNA sequence revealed expression of miR-130b as the greatest difference between radiosensitive and radioresistant groups. We subsequently evaluated miR-130b expression in our clinical OPSCC cases. Values of miR-130b >5.372 (low expression), determined from receiver operating characteristic curve analyses, were associated with significantly longer progression-free survival and overall survival ( p  = .006, p  = .04, respectively). Conclusions and significance: Our results suggest that miR-130b has potential as a biomarker for the radiosensitivity of HPV-negative OPSCC.